Ismail Shirvani and His Innovative Movement - Niyazov, Ahmed (Scholarya Demo Journal of Ruby, 2019)
Azerbaijan throughout its history has been the center of civilization in the Caucasus. From this point of view, his progressive contribution to the protection of territorial integrity and the establishment of friendly relations with neighboring countries is invaluable. We feel this more strongly during the research of archives made public by the will of fate in the post-Soviet period. One of these values is precisely traditional Islam, which is part of the national spiritual values. Studies show that since the 19th century, the enlightenment movement that spread on religious grounds by Sirajeddin Shirvani was of areformist character. The movement, which promotes high human principles, served to educate the people, brought traditions of living together, and at the same time brought dynamism to the national liberation movement of some Caucasian peoples. This movement, which has attracted the attention of Western researchers, is in reality a model of the “innovation” of the reformmovement in Muslim societies in the 19th century.                Reform efforts of this movement, whose ideas certainly referred to the Quran and Sunna, were directed to the will of Allah and his messenger. Gaining confidence in religious values, eliminating doubt, the domination of the Muslim way of life as a high value while respecting the universal principles of Islam, was an innovation that formed the basis of this movement. Also of great scientific movement, based on the traditions of the system of education, it has created some examples of typical region. They include the principle of the need for education, constancy in education as a lifelong development activity, the principle of humanism in education, taking into account individual personality characteristics, building plans that include the establishment of communication between societies and tolerance, the use of education and training at times onan individual basis, the basis for the implementation of education at every opportunity and everywhere.